Isolation, screening and identification of Kluyveromyces marxianus AY2 producing inulinase enzyme. (Journal of the College of Basic Education, 2022)
Forty-one yeast isolates were obtained from different sources and subjected to a set of primary and secondary screening tests to select the most efficient isolate in the production of inulinase enzyme. It was found that the isolate coded IY2 was the most efficient of these isolates. Diagnostic tests showed that this isolate belongs to Kluyveromyces marxianus